Cardiometabolic Risk Factors in Patients With Ankylosing Spondylitis - Mehmet UÇAR,; Savaş SARIKAYA,; Ümit SARP,; Yaşar TURAN,; Lütfi AKYOL,; Elif BÖREKÇİ,; Alirıza ERBAY,; Vahit DEMİR, (Archives of Rheumatology, 2015)
Objectives: This study aims to evaluate cardiometabolic risk factors in ankylosing spondylitis (AS) patients and their relationship with epicardial fat thickness (EFT). Patients and methods: The study included 50 consecutive AS patients (29 males, 21 females; mean age 40.5±9.4 years; range 25 to 60 years) with a median disease duration of 8.3 years and 50 healthy controls (33 males, 17 females; mean age 39.8±6.4 years, range 24 to 58 years). All patients’ EFT was measured with echocardiography. Results: Both body mass index and waist circumference measurements were higher in AS patients than healthy controls (25.4±3.5. vs. 24.5±2.9 kg/m2, p=0.005; 96.2±10.8 vs. 86.7±12.6 cm, p<0.001; respectively). Triglyceride levels were higher in AS patients than healthy controls (123.0±47.7 vs. 110.1±61.0 mg/dL, p=0.009; respectively). High-density lipoprotein cholesterol levels were lower in AS patients than healthy controls (41.3±7.0 vs. 51.9±7.0 mg/dL, p<0.001; respectively). The EFT of AS patients was greater (0.53±0.14 vs. 0.45±0.02 cm, p<0.001; respectively) and was positively correlated with age (r=0.420, p=0.002), disease duration (r=0.609, p<0.001), body mass index (r=0.419, p=0.002), waist circumference (r=0.469, p<0.001), and triglyceride (r=0.434, p=0.002) levels; and negatively correlated with high-density lipoprotein cholesterol levels (r= -0.662, p<0.001). Conclusion: As a cardiometabolic risk factor, EFT was greater in AS patients. EFT is a noninvasive method to evaluate cardiometabolic risk factors in AS patients.